PERKEMBANGAN SISTEM INFORMASI MANAJEMEN (SIM) DI INDONESIA - Alfatul Hisabi; Amelia Azura; Dhita Lutfiah; Nurbaiti (Bajang Institute, 2022)
Management Information System (MIS) is a systematic network in the administration and handling of information that aims to create data that will be provided to each time as a reason for making choices to achieve organizational goals. The purpose of a management information system is to provide information used in calculating the cost of services, goods, and other necessities desired by executives; provide data used in compiling, controlling, assessing, and improving consistently; Provision of data for decision making of a company. The historical background of management information systems basically cannot be separated from the development of data technology. The development of Management Information Systems (MIS) has existed for a long time but is now more developed, especially in Indonesia. Management Information System (MIS) improvements have been recognized by the Big Screen Organization. early understand that the biggest obstacles come from the center to the upper management layers, and not from the bottom board. Implementation of Management Information Systems in Indonesia that regularly deals with the public includes: Management Information Systems in educational institutions, Management Information Systems in health institutions, Management Information Systems in banking institutions.